Growth and physiological responses of submerged plant Vallisneria natans to water column ammonia nitrogen and sediment copper - Zhu, Zhengjie (PeerJ, 2016)
Background. The decline of submerged plant populations due to high heavy metal (e.g., Cu) levels in sediments and ammonia nitrogen (ammonia-N) accumulation in the freshwater column has become a significant global problem. Previous studies have evaluated the effect of ammonia-N on submerged macrophytes, but few have focused on the influence of sediment Cu on submerged macrophytes and their combined effects. Methods. In this paper, we selected three levels of ammonia-N (0, 3, and 6 mg L(−1)) and sediment Cu (25.75 ± 6.02 as the control, 125.75 ± 6.02, and 225.75 ± 6.02 mg kg(−1)), to investigate the influence of sediment Cu and ammonia-N on submerged Vallisneria natans. We measured the relative growth rate (RGR), above- and below- ground biomass, chlorophyll, non-protein thiol (NP-SH), and free proline. Results and Discussion. The below-ground biomass of V. natans decreased with increasing Cu sediment levels, suggesting that excessive sediment Cu can result in significant damage to the root of V. natans. Similarly, the above-ground biomass significantly decreased with increasing ammonia-N concentrations, indicating that excessive water ammonia-N can cause significant toxicity to the leaf of V. natans. In addition, high ammonia-N levels place a greater stress on submerged plants than sediment Cu, which is indicated by the decline of RGR and chlorophyll, and the increase of (NP-SH) and free proline. Furthermore, high sediment Cu causes ammonia-N to impose greater injury on submerged plants, and higher sediment Cu levels (Cu ≥ 125.75 mg kg(−1)) led to the tolerant values of ammonia-N for V. natans decreasing from 6 to 3 mg L(−1). This study suggests that high sediment Cu restricts the growth of plants and intensifies ammonia-N damage to V. natans.